The Consumer Culture Theory of Brands - Pennington, Robert (Cambridge Scholars Publisher, 2019)
Brands are components of consumer discourse. Marketers create them as devices to sell their products or services. However, once brands are marketed, they belong to consumers, because the latter confer relevance or recognition upon them. Brand viability depends upon significance to consumers and their brand use. This book explains what brands mean to consumers, and how they use brands for their own purpose of conveying that meaning to others. It illuminates not only how consumers use brands to communicate, but also how advertising has become an integral component of the cultural communication s.